Penggunaan Metode Cooperative Integrated Reading and Composotion (CIRC) Dalam Pembelajaran Bahasa Indonesia Untuk Meningkatkan Kemampuan Membaca Siswa Pada Kelas IV MI Mambaul Huda Ngabar Ponorogo - Iis Uun Fardiana (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2015)
In the course of learning, the use of a particular method of learning is very influential on learning outcomes to be achieved. But in reality, the Indonesian learning process at the school is still using methods tend menoton explained in front of the class were students just listen to information from the teacher, so that the learning process is not conducive and effective learning process difficult to achieve. This study focused on (1) whether the method of Cooperative Integrated Reading and Composition (CIRC) can improve students' reading ability? (2) how to use the methods Cooperative Integrated Reading and Composition (CIRC) can improve students' reading ability? The goal was to determine the use of methods Cooperative Integrated Reading and Composition (CIRC) can increase the ability to read student, knowing how teachers use methods Cooperative Integrated Reading and Composition (CIRC) to increase the ability to read students learning Indonesian in MI Mamba'ul Huda Ngabar Ponorogo. Desaian research is classroom action research (classroom action research) and the type of research is collaborative with teachers and pupils. The results showed that, using the method of Cooperative Integrated Reading and Composition (CIRC) can improve the reading skills of students learning Indonesian in MI Mamba'ul Huda Ngabar Ponorogo. It can be seen from the results of research that has been conducted by using the method of Cooperative Integrated Reading and Composition (CIRC) can improve reading ability siswadan active students in learning Kata kunci: Method of Cooperative Integrated Reading and Composition (CIRC), learning Indonesian, Reading ability